Analisis Faktor Penerimaan Mobile Banking BTN Menggunakan UTAUT 2 - Rahman, Yusman Zulfandra Fadhlur; Mukaromah, Siti; Faroqi, Asif (Jutisi : Jurnal Ilmiah Teknik Informatika dan Sistem Informasi, 2024)
The advent of Mobile Banking has revolutionized the banking industry, empowering customers to conveniently access their accounts. However, this increased reliance on the internet has also exposed a gap in understanding among some users, necessitating a thorough examination of Mobile Banking acceptance within the framework of BTN Bank. This research aims to propose and test a conceptual model that identifies the factors influencing interest and adoption of BTN's Mobile Banking services. The conceptual model is built upon the extended Unified Theory of Acceptance and Use of Technology (UTAUT2) by incorporating perceived risk as an internal factor. Structural Equation Modeling (SEM) based on Partial Least Square (PLS) is employed to analyze data collected from BTN Bank customers. The findings reveal that behavioral intention is significantly influenced by social influence and price value; however, other factors do not exhibit a significant impact on behavioral intention. These results suggest that future efforts to enhance Mobile Banking acceptance at BTN Bank should focus on strengthening social influence and price value, both of which demonstrate a positive and significant relationship with behavioral intention towards BTN's Mobile Banking services.Keywords: Mobile Banking; BTN Mobile; UTAUT 2; SEM-PLS.Â AbstrakSaat ini Mobile Banking merupakan sebuah terobosan dari sektor industri perbankan yang memudahkan nasabah mengakses akun mereka, sehingga pengguna semakin bergantung dengan internet, namun tidak semua pengguna memahaminya, sehingga perlu dilakukan pembahasan pengukuran penerimaan pada Mobile Banking BTN. Penelitian ini bertujuan untuk mengusulkan dan menguji model konseptual yang mengidentifikasi faktor yang mempengaruhi minat dan adopsi Mobile Banking BTN. Model konseptual diusulkan berdasarkan pada Unified Theory of Acceptance and Use of Technology (UTAUT2) yang diperluas (extended), dengan menambahkan perceived risk sebagai faktor internal. Structural Equation Modelling (SEM) berbasis Partial Least Square (PLS) digunakan untuk menganalisis data dari nasabah Bank BTN. Hasil penelitian menunjukkan bahwa behavioural intention secara signifikan dipengaruhi social influence, dan price value; namun faktor lain tidak memiliki dampak signifikan terhadap behavioural intention. Artinya peningkatan penerimaan Mobile Banking BTN ke depannya dapat berfokus pada faktor social influence, dan price value yang memiliki hubungan positif signifikan terhadap behavioural intention Mobile Banking BTN.Â